Everyday object lessons for youth groups : 45 strange & striking ways to get your point across to teenagers : easy-prep ideas for Sunday school, Bible studies, youth talks & more! /: 45 strange & striking ways to get your point across to teenagers : easy-prep ideas for Sunday school, Bible studies, youth talks & more!. (2011) - Unknown
No abstract available